2013
DOI: 10.1002/ajp.22137
|View full text |Cite
|
Sign up to set email alerts
|

Diet, Activity, Habitat Use, and Ranging of Two Neighboring Groups of Food‐Enhanced Long‐Tailed Macaques (Macaca fascicularis)

Abstract: We conducted observations of two neighboring groups of food-enhanced long-tailed macaques (Macaca fascicularis) over a period of one year. We examined their diet, behavior, habitat use, and ranging and how within-population variability reflected differential utilization of anthropogenic food resources. The group that consumed more anthropogenic food spent less time feeding on wild fruits and flowers, less time resting, and more time locomoting. They used forest habitats less often, and had a larger total home … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 48 publications
(81 reference statements)
5
54
1
Order By: Relevance
“…However, this is not always the case, because provisioned primates have also been shown to spend more time feeding as they have access to natural food resources [Boug et al, 1994;Kogenezawa and Imaki, 1999;Ram et al, 2003;Sabbatini et al, 2008;Ilham et al, 2017]. For example, Sha and Hanya [2013a] found that a group of long-tailed macaques that consumed more anthropogenic food, but also ate natural foods, spent more time feeding than a neighboring one that ate less human-derived food. We speculate that this was the case for our study.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…However, this is not always the case, because provisioned primates have also been shown to spend more time feeding as they have access to natural food resources [Boug et al, 1994;Kogenezawa and Imaki, 1999;Ram et al, 2003;Sabbatini et al, 2008;Ilham et al, 2017]. For example, Sha and Hanya [2013a] found that a group of long-tailed macaques that consumed more anthropogenic food, but also ate natural foods, spent more time feeding than a neighboring one that ate less human-derived food. We speculate that this was the case for our study.…”
Section: Discussionmentioning
confidence: 97%
“…In the highly provisioned site, the amount of provisioned food is proportional to the number of tourists [Brotcorne, 2009;Fuentes et al, 2011]. Under this condition, as their foraging strategy, the macaques increase the time they spend searching for and eating the food [Ménard and Vallet, 1997;Sha and Hanya, 2013a]. At GM, more than 1,000 tourists visit in a month, and they give approximately 520 kg of provisioned food a month, whereas the corresponding value at GP was only about 48 kg a month [Ilham et al, 2017].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations